Destruction of perfluorooctanesulfonate (PFOS) in a batch supercritical water oxidation reactor. (September 2021) - Pinkard, Brian R.; Shetty, Shreyas; Stritzinger, Derek; Bellona, Christopher; Novosselov, Igor V.
Abstract: Effective technologies are needed for the destruction of per- and polyfluoroalkyl substances (PFAS). One promising technology is supercritical water oxidation (SCWO), which can be accommodated in batch or continuous reactors. Many PFAS-laden wastes consist primarily of solid particles, and batch SCWO processing may offer safe end-of-life PFAS destruction for these feedstocks. In this study, perfluorooctanesulfonate (PFOS) is reacted via supercritical water oxidation in a batch reactor at temperatures between 425 and 500 °C and residence times from 0 to 60 min, to determine the effect of both parameters on the extent of destruction and defluorination. Analysis of liquid products via targeted LC-QToF-MS does not indicate production of intermediate fluorocarbons. However, a low fluorine mass balance at temperatures of 425 and 450 °C may indicate the existence of fluorinated species in the gaseous and/or liquid product which are not detected by targeted analysis. Destruction and defluorination efficiencies are determined for each tested condition, with a maximum 70.0% PFOS destruction and 78.2% defluorination achieved after 60 min of reaction at 500 °C. Highlights: PFOS destruction is demonstrated with carbon-fluorine bond cleavage. Batch SCWO processing shown to achieve 70% PFOS destruction at 500 °C. Reaction mechanisms proposed involving radical-driven C–S bond cleavage.